Antioxidant Activity of the Extractof Tropical Rhizomes - Umar Santoso (Indonesian Association of Food Technologists, 2004)
The objectives of the present research was to evaluate antioxidant activity of the extracts of several rhizomes, i.e., kencur (Kaempheria galanga), laos (Alpinia galangan), temulawak (Curcuma xanthorrhiza), temugiring (C. viridoflora), temuireng (C. aeruenosa), temukunci (Boesembergia pandurata), ginger (Zingiber officinalle), and turmeric (C. domestica). A certain quality of powdered sample was extracted with acetone and with ethanol. After evaporation the extracts were dissolved in methanol at a given concentration and then assayed for radical scavenging activity by DPPH method. The extracts were then evaluated for antioxidant activity in linoleic acid system by monitoring peroxide value. The results show that among the ethanolic extracts, radical scavenging activity of ginger was the most potent, followed by temulawak, while kencur was the lowest. Compared with BHA (300 µg/mL), radical scavenging activity of ethanolic extract (1%) of rhizomes were higher except temuireng and kencur. Among the acetone extracts, the highest and the lowest activity were also ginger and kencur, respectively. In linoleic acid buffer system, the trend of the activity among the extracts of rhizomes were also the same as monitored by peroxide value.